EVALUATION OF ROAD GEOMETRIC DESIGN IN THE CANGAR HOT SPRING TOURIST AREA OF BATU CITY - Riska Dwi Silfiani; Nain Dhaniarti Raharjo; Dandung Novianto (Jurusan Teknik Sipil Politeknik Negeri Malang, 2024)
±12-km Jalan Arjuno – Jalan Sumberbrantas Batu is a collector road with quite busy traffic. There are a lot of bends, climbs and also quite sharp descents that make this road uncomfortable for users. The purpose of this article is to redesign the road geometric to comply with applicable design criteria. The results of direct surveys and calculations using existing coordinate data showed that Jalan Arjuno – Jalan Sumberbrantas has ±93 bends consisting of 26 F-C types and 67 S-C-S types. Having calculated the radius of the bends according to the design criteria, it turns out that the existing R value does not meet the minimum R, and the existing road width also does not meet the PDGJ 2021 design criteria. After redesigning according to the Road Geometric Design Guidelines (or PDGJ 2021), it was found 31 S-C-S bends, and 28 vertical curves consisting of 15 sag vertical curves, and 13 crest vertical curves.